Empowering vocational education in Georgia : insights into the German-Georgian research project VoCasian - Bünning, Frank [Herausgeber]; Hennige, Tamara [Herausgeber] (wbv Media GmbH & Co. KG, 2025)
"In a globalized world, education, especially vocational education and training, is becoming increasingly important for economic growth and social stability. Internationalization has become a central topic in this field and can be considered a key aspect for a sustainable education system. Many countries, including developing and newly industrializing countries as well as countries with school-based vocational education and training systems, are undertaking reform efforts in order to meet the growing qualification requirements and increase the employability of young people. The increased competitiveness of the TVET system that this aims to achieve is set to influence the competitiveness of local SMEs in the country as well. One example of such reform efforts is Georgia. Otto von Guericke University Magdeburg is supporting the Georgian vocational training reform by building up and increasing capacities for vocational training research. Local universities are brought together with the Georgian Ministry of Education, business stakeholders and German TVET experts in order to achieve sustainable and multiplicative effects. The project includes the establishment of a doctoral program at the partner university in Tbilisi. The results will be summarized in this book, combining the national perspective with international development trends in the academization of teachers in vocational education and training." (Publisher, BIBB-Doku)
Keywords: I 1 Internationale Berufsbildung; T 1 Forschungsrichtungen; S 1.4 Hochschulbildung; I 2.1 Deutschland; I 2.2.2 Osteuropa; 370; Berufsbildungsforschung; Berufsbildung; Internationale Zusammenarbeit; Berufsbildungssystem; Hochschulbildung; Promotion; Lehrerbildung; Nachhaltige Entwicklung; Digitalisierung; Georgien; Bundesrepublik Deutschland